Approximately Multiplicative Functionals on the Spaces of Formal Power Series - F. Ershad; S. H. Petroudi (Abstract and Applied Analysis)
We characterize the conditions under which approximately multiplicative functionals are near multiplicative functionals on weighted Hardy spaces.